A Psychophysical Exploration of the Perception of Emotion from Abstract Art. (January 2014) - Dubal, Stéphanie; Lerebours, Aure-Elise; Taffou, Marine; Pelletier, Jérôme; Escande, Yolaine; Knoblauch, Kenneth
Centuries ago, western philosophers of art proposed that an artifact may express emotion. The much older tradition of Chinese calligraphy and landscape painting sees in the brushstroke a central element of the emotional expressiveness of pictorial art. How emotion is detected and perceived from artwork is a current subject of exploration in psychology. We used Signal Detection Theory to determine whether or not naive subjects were able to detect the emotional classification proposed by an artist. Thirty pairs of Chinese characters were produced by an artist so as to render the same Chinese sign with different emotional expressive intensities: one with low emotional expressivity and a second with high emotional expressivity. Twenty-two participants were asked to rate emotional intensity on a 5-point scale while viewing each calligraphy. d', a sensitivity measure reflecting the capacity to detect a signal from a noisy background, was estimated from ROC curves. If the participants categorized the stimuli according to the artist's classification (or in direct opposition), d' would differ significantly from 0. Sixteen of the participants had d' values significantly different from 0, thereby showing that they discriminated the emotional categorization of the calligraphy. Those results indicate a significant sensitivity to the emotion expressed in a Chinese calligraphy by a non-Chinese speaking population ignorant of the art of calligraphy and the artist's intention.